Studies in the quantity theory of money - Friedman, Milton (Chicago : University of Chicago, 1956)
The book contains the views of scholars on money. Such as on the theory of money; Inflation; Hyperinflation and money in German and United States.
This volume is a publication of the Workshop in Money and Banking. Studies in Economics of the Economics Research Center of the University of Chicago.
Includes index
usc 18/8/17
Loans
Keywords: Quantity theory of money; Inflation (Finance)